A borrowing cost model for effective performance of SMEs in Uganda - Tumwine, Sulait; Akisimire, Richard; Kamukama, Nixon; Mutaremwa, Gad (World Journal of Entrepreneurship, Management and Sustainable Development., 2015)
Purpose – The purpose of this paper is to develop an effective cost borrowing model of qualitative factors that are relevant to micro and small enterprises (SMEs) better performance. Design/methodology/approach – A valid research instrument was utilized to conduct a survey on 359 SMEs (131 retail businesses, 125 service businesses, 48 farming businesses and 55 other businesses) and 897 respondents that are representative of 397 SMEs and 1,087 respondents. Correlation and regression analysis were conducted to ascertain the validity of the hypotheses. Findings – It was established that cost of borrowing elements (interest rate and loan processing costs) are associated with SME performance. Furthermore, cost of borrowing as a whole account for 31.1 percent of the variation in performance Uganda’s SMEs. Research limitations/implications – Only a single research methodological approach was employed, future research through interviews could be undertaken to triangulate. Multiple respondents in SMEs (owner, manager and cashier) were studied neglecting others. Furthermore, the study used the cross-sectional approach – a longitudinal approach should be employed to study the trend over years. Finally, cost of borrowing was studied and by the virtual of the results, there are other factors that contribute to SME performance that were not part of this study. Practical implications – There is need to intensify initiatives to encourage greater understanding and acceptance of cost of borrowing, select appropriate elements that includes interest rate and loan processing costs in order to have affordable source of financing to establish and grow SMEs, provide employment, competitive and contribute to countries GDP. Originality/value – This is the first paper in Sub-Saharan Africa to test empirically the relationship between cost of borrowing and performance of SMEs in the Ugandan context.
Keywords: Performance; SME; Cost of borrowing; Interest rate; Loan processing fee; Membership fee